Analisis Pengaruh Organizational Trust dan Entrepreneurial Leadership terhadap Employee Engagement di Kementerian untuk Pertahanan Negara - Ivan Yulivan (Politeknik Ganesha Medan, 2022)
This study aims to analyze the effect of organizational trust and entrepreneurial leadership on employee engagement in the ministry for national defense. This study uses a mix-method by combining quantitative and qualitative approaches. Data collection was carried out by distributing questionnaires to 335 permanent employees in the ministry of defense of the Republic of Indonesia. Quantitative data analysis was carried out using a path analysis trimming model. The results of this study indicate that entrepreneurial leadership has a direct and positive effect on employee engagement from the path coefficient ry1 of 0.445. In addition, organizational trust has a direct positive effect on employee engagement from the path coefficient ry2 of 0.460. Organizational trust contributes more to the realization of engaged employees of the ministry of defense through maintaining consistency, integrity, and loyalty as well as increasing competence and openness. Entrepreneurial leadership is a choice of leadership model that is able to direct and grow employee trust. Employees who trust will contribute optimally to the achievement of organizational goals, because with high trust employees will become very involved with high morale and proud to work for the organization. Thus, organizations need leadership to develop a conducive work environment and build motivation for members to produce the expected feedback from various aspects.